2012
DOI: 10.1007/s12671-012-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness to Enhance Athletic Performance: Theoretical Considerations and Possible Impact Mechanisms

Abstract: Top athletes face various challenges in their career on and off the sports field. Sport psychologists teach techniques to help athletes to cope with these challenges. Over the last 30 years, the techniques used stem mainly from psychological skills training (PST), which is influenced mainly from cognitive-behavioral theories. Recently, interest in mindfulness-based interventions has increased in sport psychology. This article identifies the limits of PST and presents theoretical considerations how mindfulnessb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
175
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(214 citation statements)
references
References 69 publications
(98 reference statements)
7
175
0
10
Order By: Relevance
“…First, some conceptual problems with the measurement of components of mental training emerged. The results of Study 1 confirmed some of the problems identified by other authors (Birrer et al 2012;Vealey 2007), i.e., the distinction between mental skills and mental techniques. Second, SMTQ can fall short for some more sophisticated research questions or practical applications.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…First, some conceptual problems with the measurement of components of mental training emerged. The results of Study 1 confirmed some of the problems identified by other authors (Birrer et al 2012;Vealey 2007), i.e., the distinction between mental skills and mental techniques. Second, SMTQ can fall short for some more sophisticated research questions or practical applications.…”
Section: Discussionsupporting
confidence: 81%
“…In line with these objectives, we focused on creating a brief questionnaire targeting mental training that could be used in the sport field. Additionally, we followed theoretical suggestion that mental training questionnaires should account for distinctions between skills and techniques (Birrer et al 2012;Vealey 2007). Our questionnaire development process followed a recommendation that testing the reliability and validity of measures should be based on four stages (Netemeyer et al 2003).…”
Section: Mental Training Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The inevitable pressure felt by athletes to enhance performance and to always be Bking of the mountain^aggravates pre-competition anxiety and everyday anxiety (Terry and Slade 1995). Via (a) present-centered attention and (b) acceptance of experience, mindfulness meditation has been found to be effective in achieving optimal athletic performance through decreasing the level of anxiety, ruminative thinking, and enhancing the experience of flow (see Birrer et al 2012 andPineau et al 2014, for a review). The key element of mindfulness is indeed the nonjudgmental focus of one's attention on the experience that takes place in the here and now (Kabat-Zinn 1994).…”
Section: Introductionmentioning
confidence: 99%
“…De beskrives som mennesker med høy bevissthet omkring alle stimuli, men opplever samtidig faerre distraksjoner og reagerer mindre reaktivt i møte med følelser (Bishop et al, 2004;Brown, Ryan, & Creswell, 2007). Siden dette også er ønskelige egenskaper i idrettssammenheng for å bedre prestasjonene og redusere de negative konsekvensene av stress, har det å vaere mindful blitt sett på som et fordelaktig trekk (Birrer, Rôthlin, & Morgan, 2012). Studier på normalbefolkningen viser at å vaere mindful innebaerer økt sensitivitet til relevant informasjon, mindre sårbarhet for distraksjoner og mer effektiv oppgaveløsning (Tang, Holzel, & Posner, 2015).…”
Section: Introduksjonunclassified